Strategi Pemasaran Islam untuk Meningkatkan Penjualan Produk Garam; Studi di PT Garam Samudra Sunan Drajat - Muhammad Lucky P (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Abstrac: The most important part in selling a product is marketing. To achieve its goals, a company must have a strategy. To get and retain consumers, a company must be able to maintain consumer trust so as to give birth to a good image and finally can form customer satisfaction and loyalty so as to maintain the company's performance on an ongoing basis. To maintain consumer trust, a marketing strategy is needed that applies Islamic values ​​in every stage of marketing and operating the company. Marketing strategy greatly affects how sales targets are achieved. Is it increasing or even stagnation and even experiencing a decrease in sales turnover. This research is a qualitative research with an approach that aims to analyze the Islamic marketing strategy carried out by PT Samudra Sunan Drajat and find out the analysis of the potential of PT Samudra Sunan Drajat in increasing sales of salt products. Data collection techniques used in this study were interviews and observation. The marketing division team was used as respondents and resource persons in digging for information on how Islamic marketing strategies have been carried out by the company. The results of this study show that the Islamic marketing strategy at PT Samudra Sunan drajat is imitating the marketing practices of the Prophet Muhammad by using the analysis of marketing mix variables with the characteristics of the Prophet Muhammad: Products sold are of local quality, Determination of a price according to product quality, in increasing trust PT. Samudra Sunan Drajat applies the right of Khiyar or the right to return goods with due time, a very comfortable and very strategic place so that it is easy to produce and easily accessible because it is in the north coast area, and promotes products using social media such as Instagram and Facebook with video ads and Realpict (original image). From the results of research using SWOT analysis at PT Samudra Sunan drajat, that the implementation of PT Samudra Sunan drajat's strategy has many opportunities and strengths so that it can seize and take advantage of existing opportunities while minimizing weaknesses and overcoming various threats.